Scandal and Democracy Media Politics in Indonesia - Mary, McCoy (Cornell University Press, 2019)
After a nation has transitioned from authoritarianism to democracy, how are democratic norms most effectively fostered and maintained? This book uses as its case study Indonesia after the fall of the dictator Suharto to reveal that a contentious, even scandal-obsessed press can actually prove extremely useful for an emergent democracy. A society that can tolerate and protect journalists willing to expose corruption and scandal among elites is one, the author finds, in which ordinary citizens are willing to believe in and support other democratic institutions. Based on extensive interviews and research in Indonesia, this book offers a new and surprising perspective on the role of the press and the nature of scandal-driven journalism in fledgling democracies.